Veterinarians in a Changing Global Climate: Educational Disconnect and a Path Forward - Kramer, Collin G.; McCaw, Katherine A.; Zarestky, Jill; Duncan, Colleen G. (Frontiers in Veterinary Science, 2020)
Objective: To synthesize the beliefs, knowledge and interest of veterinarians on the relationship between veterinary medicine and climate change, with the intent to identify any educational gaps and opportunities. Sample: Responses from 560 U.S., and 54 non-U.S. veterinarians. Procedures: An anonymous, online survey of veterinarians was distributed through electronic media, state and professional associations, and a veterinary magazine advertisement. The survey was conducted between July 1st and December 31st of 2019. Results: Overall, veterinary respondents were confident that climate change is happening, is caused by human activities, and is impacting both human and animal health. Veterinarians also agreed that the profession should have an advocacy role in educating the public on climate change and its health impacts, particularly in clinical practices where environmental sustainability promotion can be shared with clients. Although veterinarians agreed the profession needs to be involved with climate change advocacy, most reported having had no educational opportunities within their veterinary medicine curriculum or access to continuing education on climate change. Conclusions and Clinical Relevance: The results highlight the need for the development of educational opportunities on the topic of climate change such that veterinarians are equipped to address their concerns about current and future animal health threats.